New trials to make camel mozzarella (Experimental biology, 2015)
Mozzarella, one of the most consumed cheeses in the world was traditionally done with cow milk. The use of camel milk was tried in the present study. All technological production chain is presented in this work. For clotting camel milk,Chy-Max M1000 (Chr Hansen ® Denmark) was used. For lactic culture,mesophilic starters (CoquardTM, France) were used. On average, camel mozzarella yield was 7,05% and the global composition on fat, protein, lactose, ash, total solids was 18,78±1,58, 30,02±1,72, 0, 3,36±0,45, 53,79±2,34% respectively. Microbiological control showed absence of Salmonella, Listeria, Staphylococcus in all studied cheeses. Globally composition is closed to buffalo or cow mozzarella, but the texture of camel mozzarella is quite different. Further studies are needed to describe rheological properties of camel mozzarella.
Keywords: camel milk; mozzarella; cheese making; technology